Analisis Perbandingan Sistem Penggajian Berbasis Desktop dan Berbasis Web pada Pengadilan Agama Surabaya - Puspita, Nanda Eka; Umarella, Barus (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This research aims to determine the payroll system using Web Salary at the Surabaya Religious Court and to analyze whether the payroll accounting system at the Surabaya Religious Court has been implemented effectively and efficiently so that it does not hinder employee performance. Before using Web Salary, the Surabaya Religious Court processed payroll using the GPP (desktop) application. The payroll system process using Web Salary is a transition from using the GPP Application (desktop) so it requires adjustments in the process. The research used by the author is descriptive qualitative research. Meanwhile, data collection techniques use observation, interviews and documentation studies. The research results show that the payroll system using Web Salaries at the Surabaya Religious Court is effective and efficient, and in accordance with the provisions regulated by the government. The Web Salary payroll system is more profitable, because it can be accessed anywhere and anytime. So this can make it easier to process salaries. Apart from that, it can also minimize salary calculation errors, because double checking has been carried out before being submitted to the KPPN. Using Web Salary also minimizes fraud or fraud committed by the financial management department, because each section already has separate user access from the others in processing salary data. This research is useful information for writers and agencies (Surabaya Religious Court employees) regarding the payroll system.